Pengembangan instrumen pengukuran kesehatan mental (mental health inventory) setelah pandemi Covid-19 pada siswa SMP - Elmispa Rabuni Br Sembiring; Nyoman Dantes; Kadek Suranata (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to develop an instrument for students' mental health in junior high schools. In order to fulfill this, research was carried out using the Research and Development (R&D) method. The development model used was the development of instruments from Prof. Nyoman Dantes with 10 steps of development, namely: 1) setting test objectives, 2) analysis of references and other learning resources, 3) compiling grids, 4) writing test items, 5) examining questions (conceptual validity), 6) revision/improvement questions, 7) limited test reproduction, 8) initial test trials and core trials (empirical validity), 9) analysis of test results (validity tests), and 10) assembling test items into tests. In testing the validity of the researcher used the Lawshe Formula with 3 Counseling Guidance lecturers and 2 experts in the field of mental health to test the appropriateness of the developed instrument containing 50 questions. To test the level of validity in a limited way, the researcher used Product Moment correlation with the help of the SPSS program which involved 60 respondents, to test the wider validity, the researcher involved 250 respondents. To test the reliability, researchers used Alpha Cronbach involving 250 respondents, while the data collection was aimed at class XI at Junior High School 2 Singaraja and Junior High School 6 Singaraja which were drawn randomly via Google form. In the distribution, the CVI value was 1 and the reliability was 0.963 so that it was included in the very high category and the instrument was declared feasible for measuring students' mental health.